Compaction and Moisture suction effects on soil strength and crop emergence - AINA, P. O.; FAPOHUNDA, H. O.; IDOWU, J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Laboratory studies were conducted to determine the effects of four levels of soil compaction and five moisture suctions on the relationship between penetrometer soil strength and emergence of maize and cowpea seedlings for five contrasting soils of Western Nigeria. Compaction (bulk density) and moisture suction accounted for 75- 88% of observed variation in soil strength and affected seedling emergence at specified soil strengths. The effect of compaction or moisture suction on the relation of seedling emergence to soil strength depended on soil and crop species. The rate of cowpea seedling emergence, which was about two-thirds that of maize, was more adversely affected by compaction than by high moisture suction. Cowpea emergence ceased when soil strengths exceeded 8 kg/cm2 in the clay loam or 10 kg/cm2 in the sandy clay loam and sandy loams, while corresponding values for maize were 14 kg/cm 2 for the clay loam and 18 kg/cm 2 for the other soils.